2022
DOI: 10.7717/peerj.12665
|View full text |Cite
|
Sign up to set email alerts
|

The association between non-suicidal self-injury and negative life events in children and adolescents in underdeveloped regions of south-western China

Abstract: Background The association between negative life events and Non-suicidal self-injury (NSSI) in children and adolescents has been extensively discussed. Nevertheless, little is known about the relationship between negative life events and repetition and severity of NSSI. This survey aims to understand the association between NSSI prevalence, severity, repetition and the negative life events in children and adolescents in underdeveloped regions in south-western China. Methods In this population-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“… 9 The high prevalence of NSSI seriously endangers the physical and mental health of adolescents and has a huge social burden, which has attracted the attention of researchers. A large number of studies on adolescent NSSI have been published in recent years, and although it has been established that NSSI is associated with complex psychosocial factors, such as anxiety, depression, child abuse, autism, and negative life events, 5 , 10 , 11 there is no unified explanation for the occurrence of NSSI. Negative life events refer to changes in individuals’ family, work, and/or study environments that may cause negative psychological and physiological outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 The high prevalence of NSSI seriously endangers the physical and mental health of adolescents and has a huge social burden, which has attracted the attention of researchers. A large number of studies on adolescent NSSI have been published in recent years, and although it has been established that NSSI is associated with complex psychosocial factors, such as anxiety, depression, child abuse, autism, and negative life events, 5 , 10 , 11 there is no unified explanation for the occurrence of NSSI. Negative life events refer to changes in individuals’ family, work, and/or study environments that may cause negative psychological and physiological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies of Chinese and Italian adolescents with NSSI consistently support a positive association between negative life events and adolescent NSSI. 11 , 14 A recent cohort study of community-based adolescents assessed distal risk factors at baseline, proximal risk factors for NSSI such as negative life events after 2 years of follow-up, and changes in adolescents’ NSSI at the end of 2.5 years of follow-up, with the result that adolescents with NSSI behaviors experienced more negative life events than those without NSSI behaviors. 15 Another multiwave longitudinal study measuring the association between NSSI and negative life events at baseline, 6 months postbaseline, and 9 months postbaseline showed that those who reported NSSI during the nine-month follow-up period had higher mean rates of negative life events.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that the relationship between peer victimization and NSSI depends on environmental factors [ 94 ]. Compared with the family environment, campus interpersonal relationships may play a more critical role in students’ emotional, cognitive, and personality development [ 95 ]. Some studies report that some teenagers use NSSI to regulate interpersonal relationships and control others [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the construction of ASLEC, interpersonal relationships include "being misunderstood, discrimination, quarrelling with classmates and friends, and losing face in public. " Interpersonal relationships during school have important influence on students' cognitive, emotional, and personality development, and may even exceed family influence (61). Poor interpersonal relationships can lead to mental health problems in adolescents (58).…”
Section: Discussionmentioning
confidence: 99%